(untitled) (Texas Journal of Medical Science, 2022)
Glaucoma today remains an urgent problem of modern ophthalmology. Despite some progress in treatment methods, a high percentage of blindness, low vision and primary disability in this disease remains. The biological basis of glaucoma is poorly understood, and the factors contributing to its progression are not fully characterized. It is not possible to completely get rid of glaucoma today, but with correct and timelytreatment, it is possible to slow down the progression of the disease. The choice of the method of therapy directly depends on the severity of the pathological changes, the symptoms present, the form of glaucoma and consists in the use of medications, surgical interventionor laser therapy. Thex-surgical method of treating glaucoma remains the leading, but at the same time associated with some complications. This article considersthe complications of surgical intervention in glaucoma and the possibility of preventing them, in particular, the role of viscoelastics